Three (re) translations of camus the stranger - Besong, Leonara (My University, 2017)
The different ways in which translators of Albert Camus’ L’Etranger (1942) have used the translation procedures outlined by Vinay and Darbelnet in translating and retaining style are analysed in this study, in an attempt to identify instances of shifts in the three English target texts considered. Research was carried out in the form of identifying stylistic traits that are peculiar, determining the procedures used to translate these and to what extent these procedures have led to deformation of style based on Berman's (1985) model of deforming tendencies in his negative analytic of translation. Furthermore, an attempt is made at identifying instances of foreignization and domestication in the three target texts. Based on the findings drawn from the paratextual and micro-textual, the research showed that the stylistic traits presented by the first translator published in 1946 were highly modified at the syntactic level including punctuation, word order and sentence structure. The study draws conclusions from the findings on the paratextual and micro-textual analyses carried out.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Translation, 2017
Keywords: Translating and interpreting; Translators